Maternal nano-titanium dioxide inhalation exposure alters placental cyclooxygenase and oxidant balance in a sexually dimorphic manner - Julie A. Griffith; Rachel D. King; Allison C. Dunn; Sara E. Lewis; Brooke A. Maxwell; Timothy R. Nurkiewicz; William T. Goldsmith; Eric E. Kelley; Elizabeth C. Bowdridge (Advances in Redox Research, 2024)
The placenta plays a critical role in nutrient-waste exchange between the maternal and fetal circulation, and thus impacts fetal growth and development. We have previously shown that nano-titanium dioxide (nano-TiO2) inhalation exposure during gestation decreased fetal female pup and placenta mass [1], which persists in the following generation [2]. In utero exposed females, once mated, their offspring's placentas had increased capacity for H2O2 production. Generation of oxidants such as hydrogen peroxide (H2O2), have been shown to impact cyclooxygenase activity, specifically metabolites such as prostacyclin (PGI2) or thromboxane (TXA2). Therefore, we hypothesized that maternal nano-TiO2 inhalation exposure during gestation results in alterations in placental production of prostacyclin and thromboxane mediated by enhanced H2O2 production in a sexually dimorphic manner. Pregnant Sprague-Dawley rats were exposed to nano-TiO2 aerosols or filtered air (sham-control) from gestational day (GD) 10–19. Dams were euthanized on GD 20, and fetal serum and placental tissue were collected based on fetal sex. Fetal placental zones (junctional zone (JZ) and labyrinth zone (LZ)) were assessed for xanthine oxidoreductase (XOR) activity, H2O2, and catalase activity, as well as 6-keto-PGF1α and TXB2 levels. Nano-TiO2 exposed fetal female LZ demonstrated significantly greater XOR activity compared to exposed males. Exposed fetal female LZ also demonstrated significantly diminished catalase activity compared to sham-control females. Exposed fetal female LZ had significantly increased abundance of 6-keto-PGF1α compared to sham-control females and increased TXB2 compared to exposed males. In the aggregate these data indicate that maternal nano-TiO2 inhalation exposure has a greater impact on redox homeostasis and PGI2/TXA2 balance in the fetal female LZ. Future studies need to address if treatment with an XO inhibitor during gestation can prevent diminished fetal female growth during maternal nano-TiO2 inhalation exposure.